2017
DOI: 10.1016/j.plabm.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the relationship between serum cortisol and serum sodium in routine clinical patients

Abstract: ObjectivesAdrenal insufficiency is an uncommon cause of hyponatraemia that should not be overlooked due to the severe consequences of an Addisonian crisis. Using the laboratory database of a large teaching hospital, we have explored the relationship between serum sodium and serum cortisol, and have estimated the frequency of hypoadrenalism in severely hyponatraemic patients.Design and methodsData were gathered over a 23 month period from the Laboratory Information Management System at the Leeds Teaching Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Working women have better cognitive function and health and lower levels of depression 30 . Those who work are able to overcome anxiety because they receive support from their family and work environment [31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working women have better cognitive function and health and lower levels of depression 30 . Those who work are able to overcome anxiety because they receive support from their family and work environment [31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Stress hyponatremia and hypernatremia are sufficient to cause an increase in cortisol. Elevated cortisol is a response to hypernatremia, and a stress response to disease 31,36,37 . Hyponatremia is caused by renal sodium hypovolemia which can stimulate antidiuretic hormone (ADH).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported Hyponatraemia as the most common electrolyte disorder recorded by clinical biochemists, and diagnosis is when the serum sodium level is below 135 mmol/L 13,20,21 . Hypernatremia has also been reported as a risk factor for mortality 21 . Results obtained from this study show a significant decrease in mean serum sodium level below normal physiologic range in the isolated males female (113 ± 2.9 mmol/L) and isolated female (125 ± 2.9 mmol/L), which indicates possible hyponatremia 22 and likely hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Their underlying signaling remains to be determined. NaCl intake and hypernatremia cause catabolism in humans and mice [2, 3, 45] and increase renal medullary urea content [2, 3]. As no catabolic patient cohorts who underwent kidney biopsies were identified, we analyzed renal gene expression in two independent datasets of short‐ and long‐term catabolic mice.…”
Section: Discussionmentioning
confidence: 99%